HUBUNGAN DUKUNGAN KELUARGA, PENGETAHUAN, DENGAN KEAKTIFAN LANJUT USIA (Lansia) MENGIKUTI KEGIATAN POSYANDU LANSIA DI WILAYAH PUSKESMAS GADING SURABAYA - NINDY VARA MEIGIA (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2020)
Minimum Standards Service is basic service quality regulation that is entitled to be obtained by every citizen. Elderly people must obtain 100% health services. Various factors can lead to low visits to the elderly posyandu in the Gading Puskesmas area in 2017. Objective: to find out the relationship between family support, knowledge, and elderly activities in the elderly posyandu in Gading Surabaya puskesmas. Method: The type of research is observational analytic with a cross-sectional design. Data processing and analysis is done by univariate and bivariate. Data collection techniques by conducting simple random sampling with a sample of 94 elderly people. Location and time of research from December 2018 at the posyandu in the Gading Surabaya health center area. Results: There is a significant value of 0,000 <0,05, so it can be concluded is have a relationship with family support, knowledge of elderly with activity following the elderly posyandu at Gading Surabaya health center